Trehalose upregulates progranulin expression in human and mouse models of GRN haploinsufficiency: a novel therapeutic lead to treat frontotemporal dementia - Holler, Christopher J. (Mol Neurodegener, 2016)
BACKGROUND: Progranulin (PGRN) is a secreted growth factor important for neuronal survival and may do so, in part, by regulating lysosome homeostasis. Mutations in the PGRN gene (GRN) are a common cause of frontotemporal lobar degeneration (FTLD) and lead to disease through PGRN haploinsufficiency. Additionally, complete loss of PGRN in humans leads to neuronal ceroid lipofuscinosis (NCL), a lysosomal storage disease. Importantly, Grn−/− mouse models recapitulate pathogenic lysosomal features of NCL. Further, GRN variants that decrease PGRN expression increase the risk of developing Alzheimer’s disease (AD) and Parkinson’s disease (PD). Together these findings demonstrate that insufficient PGRN predisposes neurons to degeneration. Therefore, compounds that increase PGRN levels are potential therapeutics for multiple neurodegenerative diseases. RESULTS: Here, we performed a cell-based screen of a library of known autophagy-lysosome modulators and identified multiple novel activators of a human GRN promoter reporter including several common mTOR inhibitors and an mTOR-independent activator of autophagy, trehalose. Secondary cellular screens identified trehalose, a natural disaccharide, as the most promising lead compound because it increased endogenous PGRN in all cell lines tested and has multiple reported neuroprotective properties. Trehalose dose-dependently increased GRN mRNA as well as intracellular and secreted PGRN in both mouse and human cell lines and this effect was independent of the transcription factor EB (TFEB). Moreover, trehalose rescued PGRN deficiency in human fibroblasts and neurons derived from induced pluripotent stem cells (iPSCs) generated from GRN mutation carriers. Finally, oral administration of trehalose to Grn haploinsufficient mice significantly increased PGRN expression in the brain. CONCLUSIONS: This work reports several novel autophagy-lysosome modulators that enhance PGRN expression and identifies trehalose as a promising therapeutic for raising PGRN levels to treat multiple neurodegenerative diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13024-016-0114-3) contains supplementary material, which is available to authorized users.